2020
DOI: 10.35683/jcm19086.64
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain resilience and design in retail supermarkets

Abstract: The Fast-Moving Consumer Goods (FMCG) industry continues to present and deliver products to end consumers irrespective of the conditions faced in the business. The nature of disruptions that unexpectedly affect retail supermarkets needs to be strategically addressed to ensure product availability to the end consumer. The Resilience concept is an important supply chain upcoming research area that can remove disruptions without affecting the retail business operations. This article sought to understand supply ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…It thus adds to the theoretical discourse on this area that can be looked into from different angles as in exploring the how CVP can be improved in the retail business through consideration of other elements other than transition in marketing strategies. The findings of the research are in agreement with other previous studies done outside Botswana (Delasay et al, 2022;Donthu & Gustafsson, 2020;Emongor & Kirsten, 2009;Eriksson & Stenius, 2020;Neboh & Mbhele, 2020;Redda, 2021) that during uncertain economic times it is important to revisit the set strategies and make changes where relevant. The research has identified practical measures that could be applied in the management of retail businesses during uncertain economic times.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It thus adds to the theoretical discourse on this area that can be looked into from different angles as in exploring the how CVP can be improved in the retail business through consideration of other elements other than transition in marketing strategies. The findings of the research are in agreement with other previous studies done outside Botswana (Delasay et al, 2022;Donthu & Gustafsson, 2020;Emongor & Kirsten, 2009;Eriksson & Stenius, 2020;Neboh & Mbhele, 2020;Redda, 2021) that during uncertain economic times it is important to revisit the set strategies and make changes where relevant. The research has identified practical measures that could be applied in the management of retail businesses during uncertain economic times.…”
Section: Discussionsupporting
confidence: 90%
“…Studies (Anik et al, 2021;Delasay et al, 2022) show that online shopping remains attractive due to minimal health concerns as compared to the traditional retail setup. Consumers have more in-depth knowledge about online shopping and related technologies; hence, this is a threat to the brick-and-mortar set-up due to improved efficiencies, customer awareness, and suppleness (Neboh & Mbhele, 2020).…”
Section: Growth Of E-commercementioning
confidence: 99%
“…The South African retail environment is dynamic as it is subject to new entrants, changing political and demographic forces, and technological advancements. Neboh and Mbhele (2020) are of the view that online retailing may pose a threat to the sector as it brings flexibility, efficiency, and awareness to consumers with knowledge and experience.…”
Section: The Retail Sector In South Africamentioning
confidence: 99%